Adrenal carcinoma About a case - Cardozo, Sandra; Barberousse, Carlos; Colet, Andrés; Serrat, Pilar (Cirugía del Uruguay, 2003)
Adrenocortical carcinoma is a very rare entity with very poor prognostic. This poor prognostic depends on its late diagnostic. The development of imagine studies (TAC, RMN) has allow an earlier diagnostic. This fact and radical surgery is the best option for healing. Other systemic treatments have not improved survival. This study presents the case of a 16 year old patient with a Cushing syndrome, virilization signs and a retroperitoneal tumor. Diagnostic, therapeutic and prognostic aspects of this malady are discussed